2023
DOI: 10.4018/978-1-6684-7164-7.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Physical Fitness and Exercise Using Computer-Assisted Instruction

Abstract: Empirical evidence has demonstrated the benefits of physical activity in preventing chronic diseases and premature death. Unfortunately, there is a global trend of insufficient physical activity, which was aggravated by the recent global pandemic. Although physical education is often used to promote physical activity, the transition to online education made it difficult to teach fitness and exercise from a distance due to several limiting factors. This chapter aims to respond to these challenges by implementin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The grouping variable, which determines whether an individual was assigned to a control or intervention group, played a critical role in explaining the variation in patient outcomes following health education programs for low back pain. The results of various studies including (Garcia et al, 2023)and (Hu et al, 2023) confirm the foregoing. The studies confirmed that health education interventions have also been found to result in better functional status, The results of our study suggest that health education intervention can effectively improve therapeutic posture practices and reduce low back pain among patients in Rivers state.…”
Section: Effect Of Health Education On Functional Posture Practices T...supporting
confidence: 72%
“…The grouping variable, which determines whether an individual was assigned to a control or intervention group, played a critical role in explaining the variation in patient outcomes following health education programs for low back pain. The results of various studies including (Garcia et al, 2023)and (Hu et al, 2023) confirm the foregoing. The studies confirmed that health education interventions have also been found to result in better functional status, The results of our study suggest that health education intervention can effectively improve therapeutic posture practices and reduce low back pain among patients in Rivers state.…”
Section: Effect Of Health Education On Functional Posture Practices T...supporting
confidence: 72%
“…Long-term Follow-up and Support: Continued monitoring, follow-up, and support are essential for individuals with lifestyle diseases (Garcia et al, 2023). This includes regular check-ups, medication adherence, counseling, and ongoing education to maintain healthy behaviors and manage risk factors.…”
Section: Awareness Of Lifestyle Diseasesmentioning
confidence: 99%
“…These apps can send timely reminders to users, encouraging them to record their meals, stay hydrated, or engage in physical activity. Other mobile applications use algorithms that analyze user data, such as dietary habits and exercise routines, to create personalized push notifications [61]. For example, if a user consistently logs high-calorie meals, the app may send a notification suggesting healthier alternatives.…”
Section: Real-time Monitoring and Feedbackmentioning
confidence: 99%